Integrated Management of Childhood Illness (IMCI) Approach in management of Children with High Grade Fever ≥ 39o - Sallam, Salem A; El-Mazary, Abdel-Azeem M; Osman, Ashraf M; Bahaa, Mohamed A (International Journal of Health Sciences, 2016)
Background: Fever is one of the most frequently encountered pediatric problems, accounting for 25% of visits to pediatric emergency room. There is no specific standardized approach to reach to a final diagnosis in children with fever as this may be difficult and individualized for each child. The integrated management of childhood illness (IMCI) approach is an approach designed to reach a classification rather than a specific diagnosis. Objective: Comparison between IMCI and Non-IMCI approaches in management of children with high grade fever≥ 39o. Patients and methods: This is a prospective study carried out on 50 children less than five years old presented with fever ≥ 39o attended the outpatient clinic of Minia university hospital from September 2012 to May 2014.These 50 children divided into 2 groups: group I (25 children) subjected to the (IMCI) approach and group II (25 children) subjected to the traditional approach. Results: Most of children according to the IMCI approach (64%) were classified and diagnosed during the first day, while most of children in traditional approach were diagnosed by the fourth (34%) or fifth day (20%). Sixty percent of children treated according to IMCI approach were improved clinically compared to 12% in traditional approach. Forty percent of children treated according to traditional approach had worse outcomes compared to 16% treated according to the IMCI. Conclusion: The IMCI approach can be applied upon children under five years old with high grade fever to reach to a classification, early diagnosis, much better outcomes and less daily cost than the traditional approach. Key words: Fever, Children, IMCI.